Peran etika audit dalam determinan kualitas audit di kantor akuntan publik Daerah Istimewa Yogyakarta: - - Khikmah, Siti Noor; Erlina, Devi; Yuliani, Nur Laila (Universitas Muhammadiyah Magelang, 2025)
Audit quality is a description of audit practices and results based on auditing standards and quality control standards, which is a measure of the implementation of an auditor's duties and responsibilities. This research examines the influence of competence, independence, professionalism, and leadership style on audit quality with audit ethics as a moderating variable. The population of this study is auditors who work at KAP DIY. The sampling technique in this research uses a purposive sampling method, and the data type used is primary. The selected sample was 6 KAPs or 38 respondents based on specified criteria. Statistical analysis in this research uses moderated regression analysis. The research results show that competence, independence, professionalism, and leadership style do not affect audit quality. Audit ethics cannot moderate the influence of the relationship between competence, independence, professionalism, and leadership style on audit quality.